Fall Prevention in Older Adults: Insights from Saudi Arabian Physical Therapists on the Otago Exercise Program - Alsaleh HM; Alsaad SM; Alabdulwahab SS; Vennu V; Bindawas SM (Dove Medical Press, 2024)
Hussam M Alsaleh,1,2 Saad M Alsaad,3 Sami S Alabdulwahab,1 Vishal Vennu,1 Saad M Bindawas1,4 1Department of Rehabilitation Sciences, College of Applied Medical Sciences, King Saud University, Riyadh, Saudi Arabia; 2Department of Physical Therapy, Prince Sultan Military Medical City, Riyadh, Saudi Arabia; 3Department of Family and Community Medicine, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 4King Salman Center for Disability Research, Riyadh, Saudi ArabiaCorrespondence: Saad M Bindawas, Department of Rehabilitation Sciences, College of Applied Medical Sciences, King Saud University, 10219, Riyadh, 11433, Saudi Arabia, Tel +966114696226, Email sbindawas@ksu.edu.saPurpose: Falls among older adults are a growing public health concern in Saudi Arabia. The Otago Exercise Program (OEP) is an evidence-based intervention aimed at reducing fall risk in this population. This study assessed the knowledge and attitudes of Saudi Arabian physical therapists toward the OEP and examined potential gender-based differences.Patients and Methods: A cross-sectional survey was conducted between November 2023 and April 2024, involving 120 licensed physical therapists from Saudi Arabia, recruited via Email and social media. The survey captured sociodemographic data, knowledge, and attitudes regarding the OEP. Responses were analyzed using descriptive statistics, chi-square tests, and Cramér's V to assess the strength of associations, with a significance level set at p < 0.05.Results: Most physical therapists reported knowledge of the OEP's clinical effectiveness (36.7%), cultural compatibility (35.0%), and fall prevention benefits (28.3%). Gender was not significantly associated with knowledge of clinical effectiveness (χ² = 3.84, p = 0.57), contraindications (χ² = 4.44, p = 0.48), cost-effectiveness (χ² = 4.15, p = 0.52), or fall prevention in older adults (χ² = 2.44, p = 0.78), with moderate effect sizes observed (Cramer's V = 0.233 to 0.467). Attitudes toward the OEP were generally positive, with 51.7% supporting its use in regular aging care and 45.0% expressing confidence in delivering the program. There were no significant gender differences in understanding the OEP's recommendations (χ² = 7.45, p = 0.11) or confidence in program delivery (χ² = 7.62, p = 0.10), although strong association effects were noted (Cramer's V = 0.696 and 0.680, respectively).Conclusion: This study highlights the strong knowledge and positive attitudes of Saudi physical therapists toward the OEP, underscoring its potential for integration into national healthcare strategies to improve geriatric care and reduce fall-related risks. The findings emphasize the importance of continuous professional development to address knowledge gaps and optimize the implementation of evidence-based fall prevention programs.Keywords: healthcare policy, risk reduction, fall prevention, physical therapists, older adults, Saudi Arabia